Komunikasi Mahasiswa Pengguna Brand Minded: Studi Fenomenologi di Universitas Singaperbangsa Karawang - Travianti, Elsypa Lora; Mayasari, Mayasari (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study aims to understand the communication experience of Communication Science students at Singaperbangsa University of Karawang who adopt a brand-minded lifestyle. This research uses a qualitative method with a phenomenological approach to explore how students perceive brands as part of their self-identity. Data was collected through in-depth interviews and non-participant observation with five active students from the Communication Science Program. The results show that students apply the brand-minded lifestyle in various aspects of their lives, particularly through fashion and gadgets. Brands are seen not only as products but as nonverbal communication tools that strengthen self-image and social status. Additionally, social influences such as parental influence, peer pressure, idols, and social media play a significant role in shaping the students' consumption behavior. This study provides insight into how nonverbal communication through brand usage creates deep social meaning in students' everyday lives.